Contribution of TMC6 and TMC8 (EVER1 and EVER2) variants to Cervical Cancer Susceptibility - Castro, Felipe A.; Ivansson, Emma L.; Juko-Pecirep, Ivana; Pawlita, Michael (International journal of cancer, 2012)
Cervical cancer (CxCa) is caused by persistent human papillomavirus (HPV) infection; genetic predisposition is also suspected to play a role. Our study is a targeted candidate gene follow-up based on: (i) strong clinical evidence demonstrating that mutations in the TMC6 and TMC8 (EVER1 and EVER2) genes associate with the HPV-associated disease epidermodysplasia verruciformis (EV) and (ii) recent epidemiological data suggesting a genetic susceptibility conferred by polymorphisms in such genes for skin and CxCa. Clarifying the association of the TMC6/8 genes with risk of CxCa will help in understanding why some HPV-infected women develop persistent infection, cervical lesions and eventually cancer while others do not. Twenty-two single nucleotide polymorphisms (SNPs) harboring the TMC6/8 genes were genotyped in 2,989 cases with cervical intraepithelial neoplasia grade III or invasive CxCa and 2,281 controls from the Swedish population. Association was evaluated in logistic regression models. Two SNPs displayed association with cervical disease: rs2290907 [odds ratio (OR)GGvsAA = 0.6, 95% confidence interval (95% CI): 0.3–0.9, p = 0.02)] and rs16970849 (ORAGvsGG = 0.8, 95% CI: 0.66–0.98, p = 0.03). The present data support the involvement of the TMC6/8 region in CxCa susceptibility but further analyses are needed to replicate our findings, fully characterize the region and understand the function of the genetic variants involved.
Keywords: TMC6 and TMC8; cervical cancer; infection